Propolis Standardized Extract (EPP-AF (R)), an Innovative Chemically and Biologically Reproducible Pharmaceutical Compound for Treating Wounds - Berretta, Andresa Aparecida; Nascimento, Andresa Piacezzi; Pires Bueno, Paula Carolina [UNESP]; Lima Leite Vaz, Mirela Mara de Oliveira; Marchetti, Juliana Maldonado (Ivyspring Int Publ, 2012)
The aim of this study was to develop a formulation, containing the propolis standardized extract (EPP-AF (R)), which can assist in the healing of skin lesions. To achieve this objective the antimicrobial activity and chemical composition of the propolis extract was determined. The final product was subjected to in vitro and in vivo pre-clinical evaluation. The broth macrodi-lution method was used to determine the antimicrobial activity of the extracts and formulations against the microorganisms most commonly found in burns, Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus and Staphylococcus epidermidis. Wistar rats with puncture wounded skin were used to evaluate the wound healing properties of propolis. The results of chemical and biological characterization demonstrated the batch-to-batch reproducibility of the standardized extract which is an unprecedented result. The antimicrobial and wound healing activity of the pharmaceutical studied showed the best results when samples contain 3.6% propolis, suggesting that this is the most promising composition.
Keywords: propolis; EPP-AF (R); antimicrobial activity; wound healing; pharmaceutics; reproducibility